Non-technical Losses in Brazil: Overview, Challenges, and Directions for Identification and Mitigation - Savian, Fernando de Souza; Siluk, Julio Cezar Mairesse; Bisognin Garlet, Tais; do Nascimento, Felipe Moraes; Pinheiro, Jose Renes; Vale, Zita (International Journal of Energy Economics and Policy, 2022)
Non-technical losses directly affect the electricity distribution system’s quality and create significant economic problems in developing countries. There has been an advance in Brazil’s regulations to combat this kind of loss in the last 15 years. However, the electricity consumed and not billed is still high, impacting the electricity tariff and distributors’ investment capacity and creating difficulties in developing public policies to mitigate the problem. Thus, this article seeks to present the panorama of non-technical losses in Brazil and propose legislative, regulatory, business, and academic directions. For this, 28 semi-structured interviews were carried out with specialists, resulting in identifying the main challenges for identifying and mitigating non-technical losses in Brazil and the factors that help overcome this problem. The results demonstrate that coordinated strategic actions among all stakeholders need to be developed to combat non-technical losses. The cultural change in acceptance of electricity theft needs to be one of the country’s main focuses. The main contribution is to disseminate information to regulatory and legislative authorities, government, concessionaires, and researchers to develop practical actions for mitigating non-technical losses in Brazil.